2022
DOI: 10.1155/2022/4889920
|View full text |Cite|
|
Sign up to set email alerts
|

Clinical Value of the Prognostic Nutrition Index in the Assessment of Prognosis in Critically Ill Patients with Stroke: A Retrospective Analysis

Abstract: Purpose. The purpose of study was to evaluate the association between prognostic nutritional index (PNI) and all-cause mortality of critically ill patients with stroke. Methods. Clinical data derived from Multiparameter Intelligent Monitoring in Intensive Care were analyzed. The primary endpoint was 30-day all-cause mortality; secondary endpoints were 90-day mortality and one-year cause mortality. The potential prognostic roles of PNI were analyzed by Cox proportional hazard models. The independent prognostic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 28 publications
2
23
0
Order By: Relevance
“…In our study, APACHE II and SOFA scores were higher and GCS was lower in the low PNI group than the high PNI group similar previous studies [3,23]. In addition, high APACHE II, SOFA and low GCS scores were independent risk factors for mortality.…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…In our study, APACHE II and SOFA scores were higher and GCS was lower in the low PNI group than the high PNI group similar previous studies [3,23]. In addition, high APACHE II, SOFA and low GCS scores were independent risk factors for mortality.…”
Section: Discussionsupporting
confidence: 89%
“…Malnutrition is associated with chronic inflammation. Some studies have reported that chronic inflammation is associated with arrhythmias [3,17,20]. The other mechanism is electrolyte imbalance, trace element and vitamin deficiency that can be seen in the presence of malnutrition causing arrhythmia [17,19].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations